Konflik pembangunan pabrik semen di pegunungan Kendeng, Jawa Tengah (Analisis konflik tenurial menggunakan teori konflik karl marx) - Analissa Huwaina; Anindita Prabawati; Anindya Dewi (Institute for Advanced Science Social, and Sustainable Future, 2024)
The Kendeng mountains, stretching from several regions in Central Java to East Java, have the potential for abundant limestone and groundwater resources. This poses a problem when the government and investors seek to exploit these resources for commercial purposes, while local communities and influential academics choose it as a conservation site. Based on the Governor of Central Java's Decree Number 660.1/17 of 2012 regarding the Environmental Permit for Mining Activities by PT. Semen Gresik (Persero) Tbk, which has been renamed PT. Semen Indonesia since 2012, they have been conducting mining activities in the Kendeng Mountains region. Subsequently, both the local community and environmental organizations have filed lawsuits concerning the feared deterioration of groundwater quality. This research aims to describe the conflicts arising from the rejection of the cement factory construction in Kendeng by conducting a descriptive analysis with data collection techniques from literature studies and content analysis of mass media. Karl Marx's conflict theory is employed to analyze the focus of this research. The conclusion drawn is that despite various legal efforts to address the rejection of the factory construction, in practice, decisions on construction and environmental permits for mining activities are still within the jurisdiction of local authorities.